Status of Palearctic wildfowl in Northeast and East Africa - Urban, Emil K (Wildfowl, 1993)
The status of 28 species of Palearctic wildfowl in Northeast and East Africa during the Palearctic winter is reported. Species with large annual wintering populations include Northern Shoveler estimated at 150,000-340,000, Common Coot at 40,000-260,000, Garganey 95,500-181,000, Eurasian Wigeon 50,000-132,000 and Northern Pintail 32,000-113,000. Numbers of Garganey and Pintail may be as high as 500,000 and 300,000, respectively, in some years due to west-east movements in Sahel Africa that are associated with drought. The large numbers of Shoveler suggest that eastern Africa is a major wintering area for this species. The paper also reports on key wetlands, including Lake Burullus in the Nile Delta and the Omo River Delta and upper portion of Lake Turkana, where 100,000 or more wildfowl sometimes winter annually.